Application of Teaching Methods (Ball Reflection to the Wall, Throwing Machine, in-pairs) and Eye Coordination to Increase the Drive Beating Skills on Tennis - Yasriuddin Yasriuddin; Muhammad Adnan Hudain (Universitas Negeri Makassar, 2020)
This experimental study aims to determine differences in teaching methods and eye and hand coordination of drive punch skills in playing tennis. The teaching method is divided into three, namely teaching the reflection of the ball to the wall, teaching the throwing machine, and teaching in pairs. This research was conducted at Faculty of Sports Science, Universitas Negeri Makassar. This research applied experimental method using a 2x3 factorial design. The sample of this research consist of sixty students, they are divided into six groups that consist of ten people each. The data analysis technique was the analysis of variance (ANOVA) and continued with the Tukey test at the significance level α = 0.05. The three teaching methods in this study have different influences on the drive skills in playing tennis. This research shows that in order to improve the drive skills in playing tennis, it is necessary to involve hand-eye coordination factors in which the physical condition elements mentioned above. A better influence compared to the method of teaching bounce ball to the wall and the throwing machine teaching method on the drive punch skill in playing tennis. Based on the findings in this study, it is expected to have implications for the development of teaching methods to improve punch drive skills in playing tennis.